(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The primary aim of this study was to assess the impact of including an interactive educational video on enhancing academic achievement among secondary school students in Abha Governorate. The study consisted of a sample of 64 students, with an equal distribution of 32 participants in both the experimental and control groups. The results of the study revealed a statistically significant increase in post-test scores pertaining to academic success in the experimental group as compared to the control group. Furthermore, the inquiry revealed that there was a significant improvement in the mean scores of the experimental group in terms of academic achievement, as observed from the initial assessment to the second measurement. There was no observed statistically significant disparity in academic achievement scores between the experimental group and the control group, both immediately after the intervention and over the subsequent evaluation period.